Possible impossibilities : a look at parapsychology - Hall, Elizabeth, 1929- (Boston : Houghton Mifflin, 1977)
Discusses the field of parapsychology today and the experimentation in it.
Includes index.
Keywords: Parapsychology -- Juvenile literature; Parapsychology; Parapsychology; Juvenile works